Ekspresi Warganet Merespon PPKM Darurat: Studi Kritis terhadap Komunikasi Publik Gubernur Bali - I Komang Agus Widiantara (Jurnal Riset Public Relations, 2022)
Abstract. The implementation of Emergency Community Activity Restrictions (PPKM) in Java and Bali has drawn criticism. Bali is one of the areas affected by this policy. The Emergency PPKM which aims to reduce crowds and suppress the Corona virus has been rejected by some Balinese people. This can be observed from the expressions of social media users in various forums. This expression can also be inferred from the posts of netizens who are critical and sarcastic. This study aims to examine public expressions and sentiments on the Facebook group of the Bali Medsos Parliament on the implementation of Emergency PPKM on the Island of the Gods. This public sentiment also responds to the Governor of Bali's public communication practices which were considered bad during the pandemic. The method used in this research is descriptive qualitative with a netnographic study approach (virtual ethnography). by analyzing relevant content and literature related to the topic on the Bali Medsos Parliament facebook group. The results of this study are that Warganet's expressions are depicted through various memes, illustrations, sarcastic statements to critical satire that become the dialogue of Warganet. Warganet's expressions also gave birth to perceptions in responding to Emergency PPKM. First, Warganet is critical and antipathetic to the policies of the Bali Provincial Government during Emergency PPKM. Second, the Governor of Bali is considered to have failed to voice the aspirations of the community in handling the Covid-19 pandemic. Third, the Governor of Bali is considered ridiculous for his call for people to consume alcoholic beverages mixed with coffee which has gone viral on social media. Fourth, the construction of prestigious projects has drawn criticism from netizens because the Governor of Bali is seen as insensitive to the socio-economic conditions of the community. Even netizens criticized the inhumane behavior of the security forces in closing down essential and non-essential sectors during the Emergency PPKM. Fifth, netizens voiced that the Governor of Bali, Wayan Koster, would not be re-elected in the agenda of the Governor Election in the future. Abstrak. Pemberlakukan Pembatasan Kegiatan Masyarakat (PPKM) Darurat di Pulau Jawa dan Bali menuai kritik. Bali menjadi salah satu wilayah yang terdampak terhadap kebijakan tersebut. PPKM Darurat yang bertujuan untuk mengurangi kerumunan dan menekan laju virus Corona ini mendapat penolakan sebagian masyarakat Bali. Hal tersebut bisa dicermati dari ekpresi pengguna media sosial di berbagai forum. Ekpresi tersebut juga bisa disimpulkan dari postingan para warganet yang bersifat kritis dan sarkas. Penelitian ini bertujuan untuk mengkaji ekpresi dan sentimen publik pada grup facebook Parlemen Medsos Bali terhadap penerapan PPKM Darurat di Pulau Dewata. Sentimen publik ini sekaligus merespon praktik komunikasi publik Gubernur Bali yang dinilai buruk selama pandemi berlangsung. Metode yang digunakan dalam penelitian ini yakni deskriptif kualitatif dengan pendekatan studi netnografi (etnografi virtual). dengan menganalisa konten-konten dan literatur relevan terkait topik pada grup facebook Parlemen Medsos Bali. Hasil dari penelitian ini adalah ekpresi Warganet diantaranya digambarkan melalui beragam meme, ilustrasi, pernyataan sarkas hingga sindriran kritis yang menjadi dialog para Warganet. Ekpresi Warganet juga melahirkan persepsi dalam merespon PPKM Darurat. Pertama, Warganet kritis dan antipati dengan kebijakan Pemerintah Provinsi Bali selama PPKM Darurat. Kedua, Gubernur Bali dinilai gagal suarakan aspirasi masyarakat dalam penanganan pandemi Covid-19. Ketiga, Gubernur Bali dinilai konyol atas himbauannya agar masyarakat mengkomsumsi minuman beralkohol arak campur kopi yang viral di media sosial. Keempat, pembangunan proyek prestesius menuai kritik dari warganet karena Gubernur Bali dipandang tidak peka dengan kondisi sosial ekonomi masyarakat. Bahkan warganet mengkritik prilaku kurang manusiawi aparat keamanan dalam menutup sektor esensial maupun non esensial selama PPKM Darurat berlangsung. Kelima, warganet menyuarakan agar Gubernur Bali Wayan Koster tidak dipilihlagi dalam agenda Pemilihan Gubernur di masa yang akan datang.